Private enterprise in the developing countries - Zenoff, David B. (Englewood Cliffs, N.J., Prentice-Hall, 1969)
The book examines private enterprise in the developing countries like Philippines, India and some countries in the Middle East, Latin America and Africa.
Includes bibliographical footnotes.
lje 17/01/2018
Loans
Keywords: Investments, Foreign; Private enterprise; Developing countries